Painting as a questioning - Zilio, Carlos (PORTO ARTE: Revista de Artes Visuais, 2013)
This article analyzes the making process of my painting. Since the historical feeling of the crisis of modernity, painting has always meant to me a manner of comprehending the amplitude and meaning of the said crisis.